Halal Food In Muslim Minority Area of North Toraja Regency Muslim Tourist - Putra, Trisno Wardy; Possumah, Bayu Taufiq; Aqbar, Khaerul; Mongkito, Abdul Wahid (Jurnal Iqtisaduna, 2021)
This study describes halal-certified food for tourists visiting tourist destinations where the population is a Muslim minority. The research method used is qualitative by using interview instruments on several research informants, namely the Regional Government, the Indonesian Ulema Council, LPPOM MUI, and food stall entrepreneurs. The results of this study conclude that there are very few halal-certified food stalls. This is due to the understanding of the public who do not really understand the importance of halal certification and are constrained by the financing. Therefore, the role of the government in this case the Department of Culture and Tourism, the Indonesian Ulema Council, LPPOM MUI, and food stall entrepreneurs need to work together in providing halal food which is one of the attractions for Muslim tourists to visit North Toraja Regency.